Optimising Cold Spray Additive Manufacturing: Pressure-driven enhancement of mechanical performance in copper deposits - Steven Camilleri; Thi Thuy Tien Tran; Keita Nomoto; Andrew Duguid; Matthew Harbidge; Riyan Rashid; Kannoorpatti Krishnan; Naveen Kumar Elumalai (PLoS ONE, 2026)
Cold spray additive manufacturing (CSAM) is a solid-state process capable of producing dense metallic components without melting, making it highly attractive for copper applications requiring both electrical conductivity and mechanical integrity. In this study, the influence of spray pressure at 30 bar, 40 bar, 50 bar and 60 bar on particle velocity, microstructure, and properties of cold-sprayed copper was systematically investigated using a LightSPEE3D system. The cold spray deposits were characterised by X-ray diffraction (XRD), hardness testing, eddy current conductivity, tensile evaluation, and scanning electron microscopy (SEM). The results reveal that increasing spray pressure enhances particle velocities beyond the critical threshold for copper, leading to improved inter-particle bonding and microstructural refinement consistent with severe plastic deformation and possible continuous dynamic recrystallisation (cDRX)-assisted mechanisms. XRD analysis suggested progressive crystallite refinement and increased dislocation density with pressure, which directly correlated with improved ductility. While hardness decreased due to recovery and recrystallisation, electrical conductivity increased, likely due to improved inter-particle continuity and reduced interfacial discontinuities. Tensile testing showed a clear strength–ductility transition, with deposits at higher pressures exhibiting substantially improved ductility approaching bulk copper behaviour and fully ductile fracture morphologies. Overall, the findings identify an optimum processing window at higher spray pressures, where copper cold spray deposits achieve a balanced combination of conductivity, ductility, and strength. This study highlights the critical role of spray pressure in controlling the interplay between particle velocity, dynamic recrystallisation, and multifunctional performance in CSAM copper components. This study establishes a process–structure–property relationship linking particle velocity, XRD-derived microstructural evolution, conductivity, and tensile behaviour within a LightSPEE3D CSAM system.